Application of amidinotaurine to perovskite active layer, perovskite solar cell module and preparation methods of amidinotaurine and perovskite solar cell module
By introducing small taper taurine in the perovskite film, the problem of high density density in FA/CS Sandang ion co -mixing olty ore, and achieved more efficient load transmission and more stable photoelectric performance Essence
Patent Information
- Application Number
- CN202411496064.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-28
AI Technical Summary
There are a large number of defects in FA/Cs double cation blended perovskites, resulting in non-radiative recombination of carriers, resulting in energy loss, and reducing the device's photoelectric performance.
Introduce the introduction of cymbal taurine as an organic small molecule additive, and pass the deep energy -grade defects on the surface of the lymphosis on the surface of the Luisic acid alkali interaction mechanism, improve the crystallization and reduce the density of defects.
It significantly improves the film quality of the perovskite film, reduces the hole, increases the size of the grain, reduces the internal defects, improves the efficiency of load transmission, and enhances the optoelectronic conversion efficiency and work stability of the device.
Smart Images

Figure BDA0005101281660000151 
Figure HDA0005101281670000011 
Figure HDA0005101281670000021
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of perovskite solar cells, and particularly relates to the application of amidinotaurine in a perovskite active layer, a perovskite solar cell component and a preparation method thereof. Background Art
[0002] Organic-inorganic hybrid perovskite solar cells have made rapid progress in the past decade, with the best certified efficiency exceeding 26%, which is comparable to mature commercial photovoltaic technology. This also makes this material a strong competitor to photovoltaic materials such as copper indium gallium selenide, gallium arsenide and silicon-based materials. Perovskites based on organic-inorganic hybrid mixed cation systems have relatively good film surface morphology, crystal crystallinity, and the corresponding devices have excellent efficiency and stability, and have attracted widespread attention from researchers.
[0003] Among the many organic-inorganic hybrid mixed cation perovskite systems, FA / Cs dual cation blended perovskite has a suitable band gap (~1.5 eV) and a high absorption coefficient (greater than 10 4 cm -1 ) and excellent carrier diffusion length (3.1μm), and thus become an important research direction. In addition, by adjusting the Cs content in this component, the internal lattice stress of the perovskite can be improved, thereby improving the phase stability and carrier lifetime, reducing the Urbach energy and defect density, and achieving higher device efficiency. However, there are still a large number of defects in the FA / Cs dual cation blended perovskite, which inevitably cause non-radiative recombination of carriers, generate more energy losses, and thus reduce the photoelectric performance of the device. Summary of the invention
[0004] In order to solve the problems raised in the above background technology, the present invention provides the following technical solution: a perovskite active layer comprises perovskite and a small molecule additive, wherein the small molecule additive comprises amidinotaurine.
[0005] Furthermore, the organic small molecule additive accounts for 0.02 mol / L to 0.03 mol / L of the perovskite.
[0006] Furthermore, the organic small molecule additive accounts for 0.026 mol / L of the perovskite.
[0007] A method for preparing a perovskite active layer, comprising:
[0008] Step 1: dissolving components including formamidinium iodine, lead iodide, cesium iodide and amidinotaurine in a mixed solution of deuterated dimethyl sulfoxide and dimethylformamide to obtain a perovskite precursor solution;
[0009] Step 2: Spin coating the perovskite precursor solution;
[0010] Step 3: Add the anti-solvent dropwise onto the surface of the perovskite precursor solution and continue spin coating;
[0011] Step 4: Annealing to obtain a perovskite active layer;
[0012] The volume ratio of the mixed solution of deuterated dimethyl sulfoxide and dimethylformamide in step 1 is 1:4;
[0013] The concentration of the perovskite precursor solution is 1.25 mol / L to 1.35 mol / L;
[0014] In the perovskite precursor solution, the amount of formamidinium iodine used is 1.22 mol / L to 1.24 mol / L;
[0015] The dosage of cesium iodide is 0.055mol / L~0.075mol / L;
[0016] The dosage of lead iodide is 1.355mol / L~1.375mol / L;
[0017] The dosage of amidinotaurine is 0.02mol / L~0.03mol / L;
[0018] The spin coating speed in step 2 is 3000 rpm to 5000 rpm;
[0019] The spin coating speed in step 3 is 3000 rpm to 5000 rpm;
[0020] The annealing conditions in step 4 are as follows: the annealing temperature is 100°C to 200°C, and the annealing time is 5min to 15min;
[0021] The anti-solvent is selected from chlorobenzene or ether.
[0022] Furthermore, the concentration of the perovskite precursor solution is 1.3 mol / L.
[0023] Furthermore, in the perovskite precursor solution, the amount of formamidinium iodide used is 1.235 mol / L.
[0024] Furthermore, in the perovskite precursor solution, the amount of cesium iodide used is 0.065 mol / L.
[0025] Furthermore, in the perovskite precursor solution, the amount of lead iodide used is 1.365 mol / L.
[0026] Furthermore, in the perovskite precursor solution, the amount of amidinotaurine used is 0.026 mol / L.
[0027] Furthermore, the spin coating speed in step 2 is 3500 rpm to 4500 rpm.
[0028] Furthermore, the spin coating speed in step 2 is 4000 rpm.
[0029] Furthermore, the spin coating speed in step three is 3500 rpm to 4500 rpm.
[0030] Furthermore, the spin coating speed in step three is 4000 rpm.
[0031] Furthermore, the annealing treatment condition in step 4 is: the annealing treatment temperature is: the annealing treatment temperature is 130°C to 160°C.
[0032] Furthermore, the annealing condition in step 4 is: the annealing temperature is 150°C.
[0033] Furthermore, the annealing conditions in step 4 are: the annealing temperature is: and the annealing time is 10 minutes.
[0034] Perovskite solar cells include a conductive glass substrate, an electron transport layer, a perovskite active layer, a hole transport layer, a blocking layer and a metal electrode in sequence.
[0035] Furthermore, the conductive glass substrate is ITO glass;
[0036] The electron transport layer is tin oxide;
[0037] The hole transport layer is 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (spiro-OMeTAD);
[0038] The barrier layer is molybdenum oxide;
[0039] The metal electrode is gold or silver.
[0040] Furthermore, the metal electrode is silver;
[0041] Furthermore, the thickness of the electron transport layer is 1 to 100 nm;
[0042] The thickness of the perovskite active layer is not less than 200 nm;
[0043] The thickness of the hole transport layer is 20 to 100 nm;
[0044] The thickness of the buffer layer is 3 to 20 nm;
[0045] The thickness of the metal electrode is 70 to 150 nm;
[0046] Furthermore, the thickness of the electron transport layer is 35-45 nm.
[0047] Furthermore, the thickness of the perovskite active layer is 300-400 nm.
[0048] Furthermore, the thickness of the hole transport layer is 50-80 nm.
[0049] Furthermore, the thickness of the buffer layer is 6.5-7.5 nm.
[0050] Furthermore, the thickness of the metal electrode is 90-100 nm.
[0051] The preparation method of a perovskite solar cell comprises cleaning the surface of a conductive glass substrate, spin coating an electron transport layer, spin coating a perovskite active layer, spin coating a hole transport layer, evaporating a buffer layer, and evaporating a metal electrode, and comprises the following steps:
[0052] Step 1: Clean the ITO substrate with a solvent and then dry it;
[0053] Step 2, preparation of solution;
[0054] (a) Preparation of a perovskite precursor solution: In a protective gas atmosphere, lead halide, amine halide, cesium iodide, and amidinotaurine are dissolved in a mixed solution of deuterated dimethyl sulfoxide and dimethylformamide to obtain a perovskite precursor solution;
[0055] (b) Preparation of electron transport layer solution:
[0056] Mixing a 15 mol / L tin oxide colloidal solvent and deionized water at a volume ratio of 1:3 to obtain a diluted tin oxide colloidal solution;
[0057] (c) Preparation of hole transport layer solution:
[0058] Dissolving 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (spiro-OMeTAD) in an organic solvent, chlorobenzene, to obtain a hole transport layer solution;
[0059] Step 3: Preparation of electron transport layer
[0060] In a protective gas atmosphere, the electron transport layer solution was spin-coated on the ITO substrate and annealed at 150°C for 20 min to obtain an ITO / ETL film;
[0061] Step 4: Preparation of perovskite active layer
[0062] In a protective gas atmosphere, the perovskite precursor solution is first spin-coated on the ITO / ETL film to start spin coating; then, 7 seconds before the end of spin coating, the anti-solvent is dropped onto the ITO / ETL film to continue spin coating; finally, annealing treatment is performed to obtain the perovskite active layer;
[0063] Step 5: Preparation of hole transport layer
[0064] In a protective gas atmosphere, 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (spiro-OMeTAD) was spin-coated on the perovskite active layer;
[0065] Step 6: Evaporating a barrier layer of molybdenum oxide;
[0066] Step 7: Evaporating metal electrodes.
[0067] Furthermore, the anti-solvent is chlorobenzene or ethyl ether, and the amount added in each spin coating is 70 μL;
[0068] The usage ratio of chlorobenzene solution and 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (spiro-OMeTAD) is 1 ml / 72 mg.
[0069] Further, the protective gas is selected from nitrogen;
[0070] The ITO substrate dried in the step 1 is treated with vacuum ultraviolet ozone;
[0071] The spin coating speed in step 3 is 2000 rpm to 5000 rpm.
[0072] The spin coating speed in step 4 is 3000 rpm to 5000 rpm.
[0073] The annealing conditions in step 4 are as follows: the annealing temperature is 100°C to 200°C, and the annealing time is 5min to 15min;
[0074] The evaporation conditions in step 5 are as follows: the pressure in the evaporation chamber is maintained at 2×10 -6 Below torr, evaporation at a rate of 0.01nm / s to 0.02nm / s;
[0075] The evaporation conditions in step 6 are as follows: the pressure in the evaporation chamber is maintained at 2×10 -6 Below torr, the deposition rate is 0.5nm / s to 1nm / s.
[0076] Furthermore, the spin coating speed in step three is 2500 rpm to 4000 rpm.
[0077] Furthermore, the spin coating speed in step three is 3000 rpm.
[0078] Furthermore, the spin coating speed in step 4 is 3500 rpm to 4500 rpm.
[0079] Furthermore, the spin coating speed in step 4 is 4000 rpm.
[0080] Furthermore, the annealing treatment condition in step 4 is: the annealing treatment temperature is: the annealing treatment temperature is 130°C to 160°C.
[0081] Furthermore, the annealing condition in step 4 is: the annealing temperature is 150°C.
[0082] Furthermore, the annealing conditions in step 4 are as follows: the annealing temperature is: the annealing time is 10 min
[0083] The beneficial effects of the present invention are:
[0084] 1. This technical solution proposes a strategy of introducing organic small molecule additives to improve the film quality of perovskite films, that is, introducing lead amidinotaurate molecules with a large number of lone pair electrons, which can improve the crystallization of perovskite while passivating the deep energy level defects on its surface through the Lewis acid-base interaction mechanism.
[0085] 2. The perovskite preparation method provided by this technical solution is simple to operate; and more importantly, the results show that no space charge effect is produced inside the perovskite battery modified by additives, and the carrier transport is very efficient.
[0086] 3. The perovskite film prepared by the method provided by this technical solution has good film-forming properties, large grain size, and low defect density; the perovskite solar cell prepared based on this has low energy loss, significantly improved photoelectric conversion efficiency, and significantly enhanced working stability.
[0087] 4. This technical solution simplifies the preparation process of photovoltaic thin films. By improving the quality of perovskite film formation, the photoelectric conversion efficiency and working stability of the corresponding devices are improved. It provides an effective strategy for the preparation of high-quality perovskite films.
[0088] 5. The additive contains oxygen atoms and single atoms with unpaired electrons, which can act as Lewis bases and react with unsaturated Pb on the surface of the perovskite film. 2+Coordination, effectively passivating the defects on the surface of the perovskite film. The introduction of additives effectively improves the crystallinity of the perovskite, inhibits the non-radiative recombination of carriers and does not affect the extraction efficiency of carriers, thereby improving the photoelectric conversion efficiency of the perovskite device and improving the working stability of the device; compared with the unmodified FA / Cs double cation blended perovskite, the method proposed in this technical solution greatly simplifies the preparation process of the perovskite film. The perovskite film prepared by this method has significantly reduced holes, increased grain size, effectively passivated internal defects of the perovskite, significantly inhibited the non-radiative recombination of photogenerated carriers, and significantly reduced the internal energy loss of the device. The corresponding photoelectric conversion efficiency and working stability are significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0089] Figure 1 It is a schematic diagram of the structure of the perovskite solar cell in the present invention;
[0090] Figure 2 JV curves of perovskite solar cells with and without guanyl taurine added;
[0091] Figure 3 The open circuit voltage-light intensity dependence curve of the perovskite solar cell with or without the addition of amidinotaurine;
[0092] Figure 4 The short-circuit current (JSC)-light intensity dependence curve of perovskite solar cells with or without guanyltaurine added;
[0093] Figure 5 The scanning electron micrograph of the perovskite film with amidinotaurine (0.026 mol / L) added;
[0094] Figure 6 This is a scanning electron micrograph of the perovskite film of the control group without the addition of amidinotaurine;
[0095] Figure 7 Nyquist plots of perovskite solar cells with and without guanyltaurine added;
[0096] Figure 8 This is a comparison chart of the storage stability of perovskite solar cells with and without guanyltaurine added in a nitrogen environment at room temperature.
[0097] Fig. 9 The stability of perovskite solar cells with and without guanyl taurine was tracked along the maximum power point (MPP) after hundreds of minutes in a nitrogen atmosphere at 65°C. DETAILED DESCRIPTION
[0098] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0099] See also Figure 1-9 The present invention provides the following technical solution: a perovskite active layer comprises perovskite and a small molecule additive, wherein the small molecule additive comprises amidinotaurine.
[0100] The characteristic of guanyl taurine is that it contains nitrogen and oxygen atoms that both have unpaired electrons. Perovskite has a chemical formula of ABX3, where A is a cation, including methylamine (CH3NH3 + ), formamidine (CH(NH2) 2+ or Cs + etc.; B is a divalent cation of a metal element of Group IV, including Pb 2+ Sn 2+ Or Ge 2+ etc.; X is a halogen ion or a halogen-like monovalent anion, including F - , Cl - Br - ,I - or SCN - wait.
[0101] In this embodiment, the organic small molecule additive accounts for 0.02 mol / L to 0.03 mol / L of the perovskite.
[0102] Preferably, in this embodiment, the organic small molecule additive accounts for 0.026 mol / L of the perovskite.
[0103] A method for preparing a perovskite active layer, comprising:
[0104] Step 1: dissolving components including formamidinium iodine, lead iodide, cesium iodide and amidinotaurine in a mixed solution of deuterated dimethyl sulfoxide and dimethylformamide to obtain a perovskite precursor solution;
[0105] Step 2: Spin coating the perovskite precursor solution;
[0106] Step 3: Add the anti-solvent dropwise onto the surface of the perovskite precursor solution and continue spin coating;
[0107] Step 4: Annealing to obtain a perovskite active layer;
[0108] The volume ratio of the mixed solution of deuterated dimethyl sulfoxide and dimethylformamide in step 1 is 1:4;
[0109] The concentration of the perovskite precursor solution is 1.25 mol / L to 1.35 mol / L;
[0110] In the perovskite precursor solution, the amount of formamidinium iodine used is 1.22 mol / L to 1.24 mol / L;
[0111] The dosage of cesium iodide is 0.055mol / L~0.075mol / L;
[0112] The dosage of lead iodide is 1.355mol / L~1.375mol / L;
[0113] The dosage of amidinotaurine is 0.02mol / L~0.03mol / L;
[0114] The spin coating speed in step 2 is 3000 rpm to 5000 rpm;
[0115] The spin coating speed in step 3 is 3000 rpm to 5000 rpm;
[0116] The annealing conditions in step 4 are as follows: the annealing temperature is 100°C to 200°C, and the annealing time is 5min to 15min;
[0117] The anti-solvent is selected from chlorobenzene or ether.
[0118] In this embodiment, the concentration of the perovskite precursor solution is preferably 1.3 mol / L.
[0119] In this embodiment, preferably, the dosage of formamidinium iodine in the perovskite precursor solution is 1.235 mol / L.
[0120] In this embodiment, preferably, the amount of cesium iodide in the perovskite precursor solution is 0.065 mol / L.
[0121] Preferably, in this embodiment, the amount of lead iodide in the perovskite precursor solution is 1.365 mol / L.
[0122] In this embodiment, preferably, the amount of amidinotaurine in the perovskite precursor solution is 0.026 mol / L.
[0123] In this embodiment, preferably, the spin coating speed in step 2 is 3500 rpm to 4500 rpm.
[0124] Preferably, in this embodiment, the spin coating speed in step 2 is 4000 rpm.
[0125] In this embodiment, the spin coating speed in step 3 is preferably 3500 rpm to 4500 rpm.
[0126] Preferably, in this embodiment, the spin coating speed in step three is 4000 rpm.
[0127] In this embodiment, the annealing condition in step 4 is preferably: the annealing temperature is 130° C. to 160° C.
[0128] In this embodiment, the annealing condition in step 4 is preferably: the annealing temperature is 150°C.
[0129] In this embodiment, the annealing conditions in step 4 are preferably: the annealing temperature is: and the annealing time is 10 minutes.
[0130] Perovskite solar cells include a conductive glass substrate, an electron transport layer, a perovskite active layer, a hole transport layer, a blocking layer and a metal electrode in sequence.
[0131] Furthermore, the conductive glass substrate is ITO glass;
[0132] The electron transport layer is tin oxide;
[0133] The hole transport layer is 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (spiro-OMeTAD);
[0134] The barrier layer is molybdenum oxide;
[0135] The metal electrode is gold or silver.
[0136] Preferably, in this embodiment, the metal electrode is silver.
[0137] In this embodiment, the thickness of the electron transport layer is 1 to 100 nm;
[0138] The thickness of the perovskite active layer is not less than 200 nm;
[0139] The thickness of the hole transport layer is 20 to 100 nm;
[0140] The thickness of the buffer layer is 3 to 20 nm;
[0141] The thickness of the metal electrode is 70-150 nm.
[0142] Preferably, in this embodiment, the thickness of the electron transport layer is 35-45 nm.
[0143] Preferably, in this embodiment, the thickness of the perovskite active layer is 300-400 nm.
[0144] In this embodiment, preferably, the thickness of the hole transport layer is 50-80 nm.
[0145] Preferably, in this embodiment, the thickness of the buffer layer is 6.5-7.5 nm.
[0146] Preferably, in this embodiment, the thickness of the hole transport layer is 90-100 nm.
[0147] The preparation method of a perovskite solar cell comprises cleaning the surface of a conductive glass substrate, spin coating an electron transport layer, spin coating a perovskite active layer, spin coating a hole transport layer, evaporating a buffer layer, and evaporating a metal electrode, and comprises the following steps:
[0148] Step 1: Clean the ITO substrate with a solvent and then dry it;
[0149] Step 2, preparation of solution;
[0150] (a) Preparation of a perovskite precursor solution: In a protective gas atmosphere, lead halide, amine halide, cesium iodide, and amidinotaurine are dissolved in a mixed solution of deuterated dimethyl sulfoxide and dimethylformamide to obtain a perovskite precursor solution;
[0151] (b) Preparation of electron transport layer solution:
[0152] Mixing a 15 mol / L tin oxide colloidal solvent and deionized water at a volume ratio of 1:3 to obtain a diluted tin oxide colloidal solution;
[0153] (c) Preparation of hole transport layer solution:
[0154] Dissolving 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (spiro-OMeTAD) in an organic solvent, chlorobenzene, to obtain a hole transport layer solution;
[0155] Step 3: Preparation of electron transport layer
[0156] In a protective gas atmosphere, the electron transport layer solution was spin-coated on the ITO substrate and annealed at 150°C for 20 min to obtain an ITO / ETL film;
[0157] Step 4: Preparation of perovskite active layer
[0158] In a protective gas atmosphere, the perovskite precursor solution is first spin-coated on the ITO / ETL film to start spin coating; then, 7 seconds before the end of spin coating, the anti-solvent is dropped onto the ITO / ETL film to continue spin coating; finally, annealing treatment is performed to obtain the perovskite active layer;
[0159] Step 5: Preparation of hole transport layer
[0160] In a protective gas atmosphere, 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (spiro-OMeTAD) was spin-coated on the perovskite active layer;
[0161] Step 6: Evaporating a barrier layer of molybdenum oxide;
[0162] Step 7: Evaporating metal electrodes.
[0163] Furthermore, the anti-solvent is chlorobenzene or ethyl ether, and the amount added in each spin coating is 70 μL;
[0164] The usage ratio of chlorobenzene solution and 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (spiro-OMeTAD) is 1 ml / 72 mg.
[0165] In the step (b), 15 mol / L of tin oxide colloidal solvent and deionized water are mixed and diluted in a volume ratio of 1:3 to obtain a tin oxide colloidal solvent.
[0166] In the step (c): 72 mg of spiro-OMeTAD was dissolved in 1 mL of organic solvent chlorobenzene to obtain a hole transport layer solution.
[0167] In this embodiment, the protective gas is selected from nitrogen;
[0168] The ITO substrate dried in the step 1 is treated with vacuum ultraviolet ozone;
[0169] The spin coating speed in step 3 is 2000 rpm to 5000 rpm.
[0170] The spin coating speed in step 4 is 3000 rpm to 5000 rpm.
[0171] The annealing conditions in step 4 are as follows: the annealing temperature is 100°C to 200°C, and the annealing time is 5min to 15min;
[0172] The evaporation conditions in step 5 are as follows: the pressure in the evaporation chamber is maintained at 2×10 -6 Below torr, evaporation at a rate of 0.01nm / s to 0.02nm / s;
[0173] The evaporation conditions in step 6 are as follows: the pressure in the evaporation chamber is maintained at 2×10 -6 Below torr, the deposition rate is 0.5nm / s to 1nm / s.
[0174] The specific operation of cleaning the ITO substrate in step 1 is: ultrasonic cleaning is performed once with anhydrous isopropanol, deionized water, deionized water, deionized water and anhydrous isopropanol, each for 30 minutes; then drying in a drying oven. Before use, the cleaned ITO glass needs to be treated with vacuum ultraviolet ozone (UV-Ozone). Ultraviolet ozone surface treatment can be achieved using equipment and processing conditions commonly used in the art, for example: UV-Ozone power is 200W, and the processing time is 3min.
[0175] Preferably, in this embodiment, the spin coating speed in step three is 2500 rpm to 4000 rpm.
[0176] Preferably, in this embodiment, the spin coating speed in step three is 3000 rpm.
[0177] Preferably, in this embodiment, the spin coating speed in step 4 is 3500 rpm to 4500 rpm.
[0178] Preferably, in this embodiment, the spin coating speed in step 4 is 4000 rpm.
[0179] In this embodiment, the annealing condition in step 4 is preferably: the annealing temperature is 130° C. to 160° C.
[0180] In this embodiment, the annealing condition in step 4 is preferably: the annealing temperature is 150°C.
[0181] In this embodiment, the annealing conditions in step 4 are preferably: the annealing temperature is: and the annealing time is 10 minutes.
[0182] The test instruments and test conditions used in the embodiments are:
[0183] JV curve: First, the light intensity of the solar simulator system is calibrated by the silicon photodiode and KG5 filter calibrated by the US Renewable Energy Laboratory. Then, the device is placed under the calibrated test light source using a test fixture (performed in an N2 glove box), and the JV characteristic curve of the perovskite semiconductor optoelectronic device is automatically tested by the Keithley source meter and the corresponding configured software, and the open-circuit voltage (V) is obtained from the curve. oc ), short-circuit current density (Short-circuit density, J sc ), fill factor (FF) and power conversion efficiency (PCE).
[0184] During the JV curve test, the test voltage was set to -0.2V to 1.2V, the interval was 0.02V, and the delay time was 0.1s.
[0185] The light intensity dependence test is based on the hardware and parameters of the JV curve test. The difference is that the light intensity dependence test changes the intensity of the incident light and tests the 2 Up to 100mW / cm 2 (interval 10mW / cm 2 )Parameters of the device under multiple light intensities.
[0186] The surface morphology of the perovskite was obtained by a scanning electron microscope (SEM) of the Philips XL30 FEG model. A steady-state photoluminescence (PL) system equipped with a single grating Horiba Flurology used a monochromatic xenon lamp as the excitation source and was tested based on a quartz glass SnO2 / ZnO / perovskite structure.
[0187] Electrochemical impedance spectroscopy (EIS) tests were performed based on a commercially available PIAOs testing system (Fluxim4.0).
[0188] Unless otherwise stated, all solvents and materials used in the examples were obtained from commercial sources and used without further purification.
[0189] The ITO transparent electrode glass (10Ωsq -1 ) was purchased from Youxuan Technology Co., Ltd.
[0190] Cesium iodide (CsI, purity 99.999%), molybdenum oxide (MoO3, purity 99.97%), chlorobenzene (CB, purity 99.8%) were purchased from Sigma-Aldrich. Formamidinium iodide (FAI, purity ≥ 99.5%) and spiro-OMeTAD (purity ≥ 99.5%) were purchased from Xi'an Biolight Optoelectronics Technology Co., Ltd. Amidinotaurine (purity ≥ 99%) was purchased from Aladdin. PbI2 (purity 99.99%) was purchased from Tokyo Chemical Industry. DMSO (purity 99.9%) and DMF (purity ≥ 99%) were purchased from Acros Organics. SnO2 colloidal dispersion was purchased from AlfaAesar.
[0191] The device structure of perovskite solar cells is: ITO / SnO2 / Perovskite / spiro-OMeTAD / MoO3 / Ag, such as Figure 1 shown.
[0192] The specific preparation process is as follows:
[0193] Prepare perovskite precursor solution:
[0194] Prepare FA with a concentration of 1.3 mol / L 0.95 Cs 0.05 PbI3 perovskite solution: 629.2 mg of lead iodide (PbI2), 197.9 mg of iodomethane (FAI), 16.8 mg of cesium iodide (CsI), and 4.3 mg of acetyl taurine (EA) were mixed and dissolved in 1 mL of a mixed solvent of DMF and DMSO (the control group did not add acetyl taurine, and the rest was the same). The volume ratio of deuterated dimethyl sulfoxide to dimethylformamide was 1:4. The prepared solution was placed on a constant temperature magnetic stirrer and stirred for more than 24 hours, and stored in a nitrogen glove box for later use.
[0195] Prepare electron transport layer solution:
[0196] A 15 mol / L tin oxide colloidal solvent was mixed with deionized water at a volume ratio of 1:3 to obtain a diluted tin oxide colloidal solution.
[0197] Preparation of perovskite solar cells (the experimental group and the control group have the same steps):
[0198] The ITO glass was ultrasonically cleaned in anhydrous isopropanol, deionized water, deionized water, deionized water and anhydrous isopropanol in turn, each for 30 minutes; then dried in a drying oven. Before using the cleaned ITO glass, its surface needs to be treated with vacuum ultraviolet ozone (UV-Ozone) for 3 minutes to improve wettability.
[0199] Spin coat the SnO2 colloidal dispersion to obtain the SnO2 layer at a speed of 4000 rpm for 30 seconds. Anneal the prepared glass / ITO / SnO2 / ZnO on a 150°C hot stage for 20 minutes to promote complete volatilization of the solvent. After the annealing is completed and the substrate layer is cooled to room temperature, it is transferred to a nitrogen environment glove box, and then spin coat the perovskite precursor solution to obtain a perovskite film at a speed of 4000 rpm for 35 seconds. 8 seconds before the end of spin coating, quickly drop 100 μL of chlorobenzene solution on the surface of the perovskite film. After the spin coating is completed, remove it and quickly anneal it on a 150°C hot stage for 20 minutes. Spin coat the configured spiro-OMeTAD on the perovskite layer at a speed of 4000 rpm for 20 seconds. Finally, transfer the entire film to a high vacuum evaporation equipment at a vacuum degree of 2×10 -6 In a torr environment, MoO3 with a thickness of 7nm and Ag with a thickness of 100nm were sequentially evaporated.
[0200] Current density voltage (JV) test
[0201] The current density voltage (JV) curve of the perovskite solar cells in the experimental group with guanidine taurine added and the control group without guanidine taurine added was tested. The results are shown in Figure 2 and Table 1.
[0202] Table 1. Photovoltaic parameters of devices in the experimental group and the control group
[0203]
[0204] from Figure 2 As can be seen from Table 1, the short-circuit current density of the device with the introduction of guanyl taurine small molecules increased from 24.08 to 24.26 mA / cm 2 , the open circuit voltage increased from 1.142 to 1.162V, and the fill factor increased from 78.28% to 82.16%. This result shows that the introduction of guanyl taurine can significantly suppress the defects inside the perovskite active layer to improve the carrier extraction efficiency and reduce the energy loss of the perovskite device. Finally, the photoelectric conversion efficiency of the perovskite solar cell increased from 21.56% to 23.08%.
[0205] according to Figure 2 By comparison, it can be concluded that all parameters of the perovskite device modified by amidinotaurine are significantly improved, especially the fill factor (FF) and open circuit voltage (V OC ). The photoelectric conversion efficiency of the modified device is significantly higher than that of the control device.
[0206] according to Figure 3 By comparison, it can be concluded that the slope of the curve of the device modified with amidinotaurine (1.21K BT / q) is less than that of unmodified device (1.35K B T / q); it shows that the amidinotaurine molecule has a significant effect on the defect passivation of perovskite, and the non-radiative recombination process of carriers is significantly suppressed.
[0207] according to Figure 4 By comparison, it can be found that the slope of the curve of the device modified with amidinotaurine (0.825) is almost the same as that of the unmodified device (0.823), indicating that the carrier transport process inside the two devices is relatively balanced and the space charge effect can be ignored.
[0208] contrast Figure 5 and Figure 6 After the introduction of additives, the film-forming properties of the perovskite film are better, the pores are significantly reduced, and the grain size is increased.
[0209] Figure 7 It reflects the transport and recombination characteristics of carriers. The Nyquist curve can be divided into two regions: the high-frequency region can reflect the carrier transport characteristics of the middle part of the anode and cathode of the device; the low-frequency region reflects the recombination characteristics of carriers. By comparison, it can be seen that the coincidence impedance of the device modified with amidinotaurine is much greater than that of the control group, indicating that the former has a larger coincidence resistance in the low-frequency region, and the non-radiative recombination of carriers is significantly suppressed.
[0210] according to Figure 8 By comparison, it can be seen that after 30 days of storage, the taurine-modified device can still maintain a relatively high efficiency, while the efficiency of the control group has decreased significantly.
[0211] according to Fig. 9 By comparison, it can be found that the output efficiency of the control group device decreases with continuous operation, while the experimental group with the introduction of additives still maintains almost the same efficiency as the initial after 270 minutes of continuous operation, indicating that the addition of guanyltaurine significantly improves the working stability of the device
[0212] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A perovskite active layer, comprising perovskite and a small molecule additive, characterized in that: The small molecule additive includes amidinotaurine.
2. The perovskite active layer according to claim 1, characterized in that: The organic small molecule additive accounts for 0.02 mol / L to 0.03 mol / L of the perovskite.
3. A method for preparing a perovskite active layer, comprising: Step 1: dissolving components including formamidinium iodine, lead iodide, cesium iodide and amidinotaurine in a mixed solution of deuterated dimethyl sulfoxide and dimethylformamide to obtain a perovskite precursor solution; Step 2: Spin coating the perovskite precursor solution; Step 3: Add the anti-solvent dropwise onto the surface of the perovskite precursor solution and continue spin coating; Step 4: Annealing to obtain the perovskite active layer. Features: The volume ratio of the mixed solution of deuterated dimethyl sulfoxide and dimethylformamide in step 1 is 1:4; The concentration of the perovskite precursor solution is 1.25 mol / L to 1.35 mol / L; In the perovskite precursor solution, The dosage of formamidine iodine is 1.22 mol / L to 1.24 mol / L; The dosage of cesium iodide is 0.055mol / L~0.075mol / L; The dosage of lead iodide is 1.355mol / L~1.375mol / L; The dosage of amidinotaurine is 0.02mol / L~0.03mol / L; The spin coating speed in step 2 is 3000 rpm to 5000 rpm; The spin coating speed in step 3 is 3000 rpm to 5000 rpm; The annealing conditions in step 4 are as follows: the annealing temperature is 100°C to 200°C, and the annealing time is 5min to 15min; The anti-solvent is selected from chlorobenzene or ether.
4. A perovskite solar cell, characterized in that: The method comprises, in sequence, a conductive glass substrate, an electron transport layer, a perovskite active layer according to any one of claims 1 to 2 or a perovskite active layer prepared by any one of claims 3 to 5, a hole transport layer, a barrier layer and a metal electrode.
5. The perovskite solar cell according to claim 4, characterized in that: The conductive glass substrate is ITO glass; The electron transport layer is tin oxide; The hole transport layer is 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (spiro-OMeTAD); The barrier layer is molybdenum oxide; The metal electrode is gold or silver.
6. The perovskite solar cell according to claim 5, characterized in that: The thickness of the electron transport layer is 1 to 100 nm; The thickness of the perovskite active layer is not less than 200 nm; The thickness of the hole transport layer is 20 to 100 nm; The thickness of the buffer layer is 3 to 20 nm; The thickness of the metal electrode is 70-150 nm.
7. A method for preparing a perovskite solar cell, comprising cleaning the surface of a conductive glass substrate, spin coating an electron transport layer, spin coating a perovskite active layer, spin coating a hole transport layer, evaporating a buffer layer, and evaporating a metal electrode, characterized in that: The following steps are involved: Step 1: Clean the ITO substrate with a solvent and then dry it; Step 2, preparation of solution; (a) Preparation of a perovskite precursor solution: In a protective gas atmosphere, lead halide, amine halide, cesium iodide, and amidinotaurine are dissolved in a mixed solution of deuterated dimethyl sulfoxide and dimethylformamide to obtain a perovskite precursor solution; (b) Preparation of electron transport layer solution: A 15 mol / L tin oxide colloidal solvent and deionized water were mixed at a volume ratio of 1:3 to obtain a diluted tin oxide colloidal solution; (c) Preparation of hole transport layer solution: Dissolving 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (spiro-OMeTAD) in an organic solvent, chlorobenzene, to obtain a hole transport layer solution; Step 3: Preparation of electron transport layer In a protective gas atmosphere, the electron transport layer solution was spin-coated on the ITO substrate and annealed at 150°C for 20 min to obtain an ITO / ETL film; Step 4: Preparation of perovskite active layer In a protective gas atmosphere, the perovskite precursor solution is first spin-coated on the ITO / ETL film to start spin coating; then, 7 seconds before the end of spin coating, the anti-solvent is dropped onto the ITO / ETL film to continue spin coating; finally, annealing treatment is performed to obtain the perovskite active layer; Step 5: Preparation of hole transport layer In a protective gas atmosphere, 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (spiro-OMeTAD) was spin-coated on the perovskite active layer; Step 6: Evaporating a barrier layer of molybdenum oxide; Step 7: Evaporating metal electrodes.
8. The method for preparing a perovskite solar cell according to claim 7, characterized in that: The anti-solvent is chlorobenzene or ether, and the amount added in each spin coating is 70 μL; The usage ratio of chlorobenzene solution and 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (spiro-OMeTAD) is 1 ml / 72 mg.
9. The method for preparing a perovskite solar cell according to claim 8, characterized in that: The protective gas is selected from nitrogen; The ITO substrate dried in step 1 is treated with vacuum ultraviolet ozone; The spin coating speed in step 3 is 2000 rpm to 5000 rpm; The spin coating speed in step 4 is 3000 rpm to 5000 rpm; The annealing conditions in step 4 are as follows: the annealing temperature is 100°C to 200°C, and the annealing time is 5min to 15min; The evaporation conditions in step 5 are as follows: the pressure in the evaporation chamber is maintained at 2×10 -6 Below torr, evaporation at a rate of 0.01nm / s to 0.02nm / s; The evaporation conditions in step 6 are as follows: the pressure in the evaporation chamber is maintained at 2×10 -6 Below torr, the deposition rate is 0.5nm / s to 1nm / s.